Penerapan Etika Bisnis Islam Dalam Usaha MikroMebel/UMKM - Abdul Mannan; Inayah Swasti Ratih (IZZI: Jurnal Ekonomi Islam, 2021)
This study aims to determine the concept and application of Islamic business ethics forsmall business actors. The purpose of this research is to find out how the concept ofIslamic business ethics is and how it is implemented for small business actors so thatlater it is hoped that the results of this research resume can be used as a framework ormodel for other business actors. previous research. This study uses a qualitativeresearch approach with field studies of furniture business actors in the Paiton subdistrict, Randumerak village. The results showed that the strategies implemented in theIslamic sharia business are in the micro-furniture business. The results show that Mr. H.Dawi's furniture shop business in Randumerak has implemented Islamic businessethics, both by employers and employees. In conducting business and activities,business actors have understood and implemented Islamic principles or values basedon the Al-Qur'an and Hadith. The implementation of Islamic business ethics includesfive aspects, namely, Unity (Tauhid / unity), (Equilibrium / fair balance), (Free Will),(Responsibility / Responsibility), and (Truth, Honesty / truth honesty).